2021
DOI: 10.1101/2021.03.23.436570
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial Communities Performing Hydrogen Solventogenic Metabolism of Volatile Fatty Acids

Abstract: 1AbstractBackgroundProduction of alcohols from wastes through biological processes is environmentally and economically interesting, since they can be valorized as drop-in liquid fuels, which have a high market value. Using microbial mixed cultures in such processes is of great interest since it confers more stability, a higher resistance to both toxicity and contamination, and an increased substrate flexibility. However, there is still a lack of fundamental knowledge on such microbial populations used as inocu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…In another study, alcohol dehydrogenase (ADH) production was observed in Acinetobacter strains during ethanol conversion to acetate, the primary pathway of reversion of solventogenesis. The ADH has been related to bacterial quorum sensing, and as a key stimulator for alcohol oxidation [121]. Conversely, spore formation has been reported as a survival mechanism under solventogenesis stress.…”
Section: Proteomics In the Production Of Acids And Solventsmentioning
confidence: 99%
“…In another study, alcohol dehydrogenase (ADH) production was observed in Acinetobacter strains during ethanol conversion to acetate, the primary pathway of reversion of solventogenesis. The ADH has been related to bacterial quorum sensing, and as a key stimulator for alcohol oxidation [121]. Conversely, spore formation has been reported as a survival mechanism under solventogenesis stress.…”
Section: Proteomics In the Production Of Acids And Solventsmentioning
confidence: 99%